Development of educational recreation facilities and digital promotion strategies for Arboretum Tourism Park sustainability - Danti Yuliarsi Saadjad; Ichsan Milang; Nurlaela Nurlaela; Dian Puspapratiwi; Sukma Widya Sasmi Sabbu (University of Merdeka Malang, 2025)
The Arboretum Tourism Park, located in Bumi Harapan, holds great potential to become a leading tourism destination in Central Sulawesi, particularly in Banggai. Therefore, this community service aims to assist the village government in developing the Arboretum Tourism Park through the creation of educational recreational facilities and the implementation of digital promotion strategies. The Asset-Based Community Development (ABCD) method was applied to address the partner’s needs. The results showed significant improvement in the development of educational recreational facilities, increasing from 20 percent to 90 percent, marked by the establishment of three attractions. Furthermore, technical guidance on digital promotion strategies enhanced the managers’ skills from 40 percent to 95 percent, as evidenced by the establishment of an official website and social media platforms for the park. The contribution of this program lies in increasing the park’s attractiveness, which is expected to boost tourist visits and, ultimately, contribute to improving the village economy. This program supports sustainable village-based tourism development.